Educational interventions to improve maternal‐foetal outcomes in women with gestational diabetes - Silvia Gorbán de Lapertosa; Jorge F. Elgart; Claudio D. González; Jorge Alvariñas; Paula Camin; Leonardo Mezzabotta; Susana Salzberg; Juan J. Gagliardino (Wiley, 2021)
Abstract Aims To evaluate improvement in gestational diabetes (GDM) outcomes for mothers and their offspring induced by education provided to the healthcare team (HCTM) and women with GDM, plus coordination between primary care units (PCU) and highly complex maternity (HCM) facilities. Methods Pregnant women with GDM completing control visits from first appointment until delivery were recruited in participating PCU‐HCM, in the cities of Corrientes and Buenos Aires; 263 women recruited from 2017 to mid‐2018 were assigned to the control group (CG), and 432 women recruited from mid‐2018 to 2019 to the intervention group (IG). The CG received standardized care/routine management and follow‐up, including basic information on blood glucose monitoring and insulin injection when necessary, whereas the IG received an educational program targeting HCTM and women with GDM. These courses included standards of diagnosis, prevention and treatment of GDM, plus systematic registry of clinical and metabolic indicators (fasting blood glucose, serum cholesterol and triglyceride). Data on obstetric history, preeclampsia, gestation‐induced hypertension, delivery method and newborn's body weight were also recorded Results Women in the IG showed significantly (P ≤ 0.05) lower BMI and weight gain during gestation, a trend towards lower triglyceride and caesarean sections and a significant increase in postnatal attendance for metabolic assessment. Their newborns showed significantly lower body weight and a trend towards fewer macrosomia. Conclusions These data suggest that our educational intervention plus management changes induced a favourable impact on GDM outcomes for both mothers and offspring.